Avermectins: An entirely new family of endo- and ectoparasiticides - ΧΕΙΜΩΝΑΣ Χ. (Journal of the Hellenic Veterinary Medical Society, 2019)
Avermectins, a new group of broad spectrum antiparasitic compounds, are macrocyclic dis saccharides devived by fermentation from the actinomycete Streptomyces avermitilis. A mixture that contains at least 80% 22,23-dihydroavermectin Bl a and not more than 20% 22,23- dihydroavermectin Bip, known under the generic name «ivermectin», has been proved to pocess the comparatively higher paralyzing effect on parasites than the rest six homologous avermectin compounds. Ivermectin, administered orally or subcutaneously in extremely low dosages( 100-200 mcg/kg b.w.), has high levels of broad spectrum activity against a variety of endo-and ectoparasites in several hosts, including all domesticated animals. Actually, the numerous research papers, that were published within the last three years, have shown the high efficacy of ivermectin against adult, immature and larval stages (active or inhibited) of the most important gastrointestinal or extra-intestinal, benzimidazole sensitive or resistant, nematode parasites of cattle, sheep, horses, swine, dog and poultry. Moreover, ivermectin is highly effective against mange mites, lice, cattle warbles, nasal bots, horse bots and a few ticks. In the low antiparasitic dosages used, ivermectin has a remarkable degree of safety to treated animals.